PENGEMBANGAN SISTEM APLIKASI SPD & RDK MENGGUNAKAN METODE PROTOTYPE BERBASIS WEB - Riky Firmansyah; Ilham Haryadi; Iqbal Musyaffa (CV. Multi Kreasi Media, 2024)
The Bawaslu Institution requires an efficient management system for Travel Orders (SPD) and Detailed Activity Plans (RDK) to support increasingly complex operations. The manual process currently in use has proven to be ineffective, prone to errors, and time-consuming. This research aims to develop a web based SPD & RDK application system using the prototype method. This method was chosen for its ability to produce a system that meets user needs through an iterative process involving direct user feedback. The development results show that the designed application system can automate the management of SPD and RDK, from creation and verification to reporting, thereby reducing manual errors and improving work efficiency. This web-based system also facilitates easier and more transparent access between units within the Bawaslu Institution.